A New Distributed User-Demand-Driven Location Privacy Protection Scheme for Mobile Communication Network - Jin Wang; Hao Wu; Yudian Liu (International Journal of Distributed Sensor Networks)
With the development of mobile communication networks and intelligent terminals, recent years have witnessed a rapid popularization of location-based service (LBS). While obtaining convenient services, the exploitation of mass location data is inevitably leading to a serious concern about location privacy security. Obviously, high quality of service (QoS) will result in poor location privacy protection, so that a trade-off is needed to fulfill users' individual demands for both sides. Although existing methods perform well in certain scenarios, few have considered the abovementioned balance problem. Therefore, by combining k -anonymity-based cloaking technique and obfuscation method, a new distributed user-demand-driven (DUDD) location privacy protection scheme is put forward in this paper. The basic idea is still to select a subcloaking area within the cloaking area generated by Location Anonymization Server. Moreover, by using the improved LBS system model, this paper constructs a distributed framework, in which location privacy protection is wholly occupied in server side and LBS provider is only dedicated to QoS-guarantee. In addition, normalized privacy demand and QoS metrics are given and a user-defined weight parameter is introduced to ensure location privacy security without decreasing QoS. The feasibility of the proposed method is proved through simulation.